1996
DOI: 10.1073/pnas.93.17.9282
|View full text |Cite
|
Sign up to set email alerts
|

Auxin as a positional signal in pattern formation in plants.

Abstract: By using a novel, extremely sensitive and specific gas chromatography-mass spectrometry technique we demonstrate in Pinus sylvestris (L.) trees the existence of a steep radial concentration gradient of the endogenous auxin, indole-3-acetic acid, over the lateral meristem responsible for the bulk of plant secondary growth, the vascular cambium. This is the first evidence that plant morphogens, such as indole-3-acetic acid, occur in concentration gradients over developing tissues. This finding gives evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
354
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(375 citation statements)
references
References 20 publications
17
354
0
4
Order By: Relevance
“…The magnitude of the serotonin gradient predicted from our model matches well with the reported auxin gradients, which are thought to be approximately 10-fold (Edlund et al, 1995;Uggla et al, 1996). We also compared the gradient with another likely morphogen (although one which is not GJC-related): retinoic acid.…”
Section: Comparison To Other Morphogen Gradientssupporting
confidence: 76%
“…The magnitude of the serotonin gradient predicted from our model matches well with the reported auxin gradients, which are thought to be approximately 10-fold (Edlund et al, 1995;Uggla et al, 1996). We also compared the gradient with another likely morphogen (although one which is not GJC-related): retinoic acid.…”
Section: Comparison To Other Morphogen Gradientssupporting
confidence: 76%
“…Auxin is essential for vascular tissue formation and differentiation (13,14). In leaves, it has been shown that auxin accumulates in the procambial cells (15,16), leading to the gradual canalization of auxin into the leaf vascular strands through polarization of auxin efflux carriers (4,5,17). In the shoot, it has been shown that the auxin efflux carrier PIN1 is expressed in the procambium and xylem cells, at the basal side and in a fraction of the lateral cell membranes (18).…”
mentioning
confidence: 99%
“…IAA also regulates secondary growth, which is more pronounced in trees because their longevity combined with the indeterminate growth of plants leads to a higher average plant size and biomass compared with annual plants, necessitating the reinforcement of the plant body. In this context, the formation of a radial auxin gradient with a peak in the cambium and the adjacent first few layers of xylem cells and its synergistic action with GA in wood formation have been intensively researched (Uggla et al 1996(Uggla et al , 1998Eriksson et al 2000;Israelsson et al 2005;Björklund et al 2007;Nilsson et al 2008;Mauriat and Moritz 2009;Han et al 2011;Chen et al 2013). Furthermore, GAs affect elongation growth Elias et al 2012) as well as flowering of perennial plants (Zawaski et al 2011;Randoux et al 2012).…”
Section: Approaching Tree Architecturementioning
confidence: 99%